Multifunctional SBA-15 for magnetically oriented and pH targeted delivery of ibuprofen. (1st November 2013) - Lin, H M; Xing, R; Wu, X; Jiang, P P; Jiang, J J; Qu, F Y
<x xml:space="preserve">Abstract</x> A magnetic and pH targeting drug delivery system based on the magnetic nanocomposite doping mesoporous silica material has been successfully prepared. The material exhibited highly ordered mesostructure, large Brunauer-Emmett-Teller surface area, high pore volume, regular nanoparticle morphology and superior magnetic property. The structure and properties of the magnetic mesoporous nanocomposites were characterised by X-ray diffraction, scanning electron microscope, transmission electron microscope, N2 adsorption-desorption, Fourier transform infrared spectroscopy and vibrating sample magnetometer technique. The as obtained magnetic mesoporous material was used as drug carrier, and ibuprofen was used as model drug. The releases in simulated proximal intestine fluid (pH 7·4) and simulated gastric fluid (pH 1·2) were studied. Therefore, a novel multifunctional drug delivery system with magnetically oriented and alkalescence site targeted release has been obtained.